2000
DOI: 10.1007/s004210000197
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between physical activity, physical fitness, muscle strength and nutritional state in 5- to 11-year-old children

Abstract: The purpose of the present study was to assess different aspects of physical activity and fitness in order to develop a basis for sport programmes for overweight and obese children. Eighty-eight prepubertal children (49 boys, 39 girls, 4.8-11.4 years old, 61% obese, 14% overweight and 25% normal weight) were examined. Body composition was assessed by combined use of anthropometrics and bioelectrical impedance analysis. Resting energy expenditure (REE) and total energy expenditure (TEE) were measured by indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 27 publications
(43 reference statements)
8
50
0
5
Order By: Relevance
“…[18][19][20][21][22][23][24][25] However, some of these studies were conducted with a small number of subjects, whereas others included children and adolescents in the same analyses. It has also been reported that overweight as well as obese children showed a lower physical fitness than normal children.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] However, some of these studies were conducted with a small number of subjects, whereas others included children and adolescents in the same analyses. It has also been reported that overweight as well as obese children showed a lower physical fitness than normal children.…”
Section: Discussionmentioning
confidence: 99%
“…Ravussin and colleagues (32) have shown that decreased energy expenditure precedes weight gain in morbidly obese Pima Indians. Furthermore, human obesity is significantly associated with low levels of physical exercise (12,16). It was also been proposed recently that nonexercise activity thermogenesis is an important component in human energy balance (22).…”
Section: Physiological Characterization Of New Zealand Obese Micementioning
confidence: 99%
“…Individually FLEX-HR was used to discriminate between resting and exercise HR. Total energy expenditure was measured by the FLEX-HR monitoring method as described previously 40,41 . For the remainder of the daytime, when HR was above FLEX-HR, energy expenditure was derived from the minute-by-minute recorded HR using the individual child's regression line for the VO 2 corresponding to HR 15 .…”
Section: Hr Monitoringmentioning
confidence: 99%